Menopausal symptoms and cardiovascular disease mortality in the Women's Ischemia Syndrome Evaluation (WISE). Issue 2 (February 2017) - Thurston, Rebecca C.; Johnson, B. Delia; Shufelt, Chrisandra L.; Braunstein, Glenn D.; Berga, Sarah L.; Stanczyk, Frank Z.; Pepine, Carl J.; Bittner, Vera; Reis, Steven E.; Thompson, Diane V.; Kelsey, Sheryl F.; Sopko, George; et al.
Abstract: Objective: Studies have linked vasomotor symptoms (VMS) to markers of cardiovascular disease (CVD) risk, yet few have considered clinical cardiovascular events. Data suggest that associations may depend upon the age that symptoms occur. We examined associations between VMS and cardiovascular events and endothelial function, considering age of symptom onset. Methods: The Women's Ischemia Syndrome Evaluation enrolled women referred for coronary angiography for suspected myocardial ischemia. A total of 254 women aged more than 50 years, postmenopausal, with both ovaries, not taking hormone therapy underwent a baseline evaluation, were followed annually (median = 6.0 y), and the National Death Index was searched to ascertain CVD mortality (median = 9.3 y). A subset of participants underwent brachial artery ultrasound for flow-mediated dilation (FMD). Receiver-operating curve analysis was used to determine vasomotor symptom groups (symptoms beginning < age 42 [early onset], beginning ≥42 [later onset], never) which were examined in relation to cardiovascular events and FMD in Cox proportional hazard and linear regression models. Results: Women reporting early onset VMS (HR = 3.35, 95% CI = 1.23-7.86, P  = 0.005) and women who never had VMS (HR = 2.17, 95% CI = 1.02-4.62, P  = 0.05) had higher CVD mortality than women with later onset symptoms (multivariable models). Women with early onset VMS had lower FMD than women with later onset symptoms (b = −4.31, SE = 2.10, P  = 0.04, multivariable). Conclusions: Women with signs and symptoms of ischemia who had VMS beginning early in midlife had higher CVD mortality and reduced endothelial function relative to women with later onset symptoms. Future research should evaluate the vascular phenotype of women with early midlife VMS.